On n’attrape pas les mouches avec du vinaigre - Nicolas Césard; Anie Montigny (Revue d'ethnoécologie)
The question is old and serious: how to get rid of flies? Several objects in the ethnobiology collection attempt to answer it through different methods that we shall hereby present. By considering fly swatters as traps, this selective inventory reflects the transition in their technical evolution and uses from an anthropocentric to a biocentric approach.